Virginiamycin improves phosphorus digestibility and utilization by growing-finishing pigs fed a phosphorus-deficient, corn-soybean meal diet (2007)
ABSTRACT: Evaluations of the nutritional effect of antibiotics have largely centered on effects related to the digestibility and utilization of protein and energy. The current study evaluated the potential effect of virginiamycin (VIR) on P digestibility in swine. A total of 70 barrows (mean initial BW = 51 to 64 kg) were used in 4 nutrient-balance experiments. A basal, corn-soybean meal diet that was not supplemented with any inorganic source of P was used in each experiment. In Exp.1, two diets were tested: basal vs. basal plus 11 mg/kg of VIR. In Exp. 2, four diets were used with a 2 × 2 factorial arrangement of 0 and 11 mg/kg of VIR and 0 and 750 phytase (PHY) units/kg of diet (PU/kg). Experiments 3 and 4 were the same as Exp. 2, except PHY was reduced to 300 PU/kg. For all experiments, VIR improved P digestibility (32.71 to 37.72%, P < 0.001) and Ca digestibility (54.99 to 58.30%, P = 0.002). The addition of PHY improved both P and Ca digestibility (P < 0.001); 750 PU/kg increased P digestibility 27.3% (from 34.6 to 61.9%, P < 0.001), whereas 300 PU increased it 13.8% (from 33.4 to 47.2%, P < 0.001). In an experiment conducted to evaluate the long-term effects of VIR on gut microbial profile, pigs (24 gilts and 8 barrows; mean BW = 29.1 ± 0.50 kg) were fed a simple corn-soybean meal diet for 16 wk with a 2 × 2 factorial arrangement of VIR (0 and 11 mg/kg) addition and 0.15% dicalcium phosphate deletion. The long-term feeding of VIR in both the control diet and the diet with a marginally reduced P level resulted in a change in ileal microbial profile. A positive numerical increment in the number of phytate-utilizing bacteria was observed in both the normal and P-deleted diets (log unit increments of 12.4 and 17.2% over the respective controls, P = 0.13) when VIR was added. The addition of VIR also tended to affect lactobacilli populations (maineffect, P = 0.11; interaction, P = 0.02); VIR decreased lactobacilli in the normal-P diet but did not affect this bacterial population in the P-deleted diet. In conclusion, the antibiotic VIR improves both Ca and P digestibility in pigs. The increase in digestibility is not as great as that provided by PHY, but because the potential mechanism of action (altered microbial populations) differs from that of PHY (direct addition of an enzyme), there can be a degree of additivity in P digestibility improvement when both products are used.